The effect of technological innovations, urbanization and economic growth on environmental quality: does governance matter? - Khan, Hayat; Khan, Itbar (Frontiers in Environmental Science, 2023)
Global warming and climate change have become major challenges in recent decades as a result of rapid economic growth due to increased energy use and urbanization. Environmental damage induced by energy use, urbanization, and economic growth can be overcome by technological advancement and good governance. This study examines the effect of urbanization, technological innovations, and economic growth on carbon dioxide emissions by introducing the moderating role of governance in the Belt and Road initiative countries from 2002 to 2019. By using GMM model, the results shows that urbanization, technological innovations, and FDI raise carbon dioxide emissions however, research and development increase environmental quality. This study also found that urbanization has a nonlinear relationship with carbon emission where government effectiveness exert a moderating role in the nexus between urbanization and carbon dioxide emission. This study provides important policy implications for the sample countries.